Covariance spectroscopy of molecular gases using fs pulse bursts created by modulational instability in gas-filled hollow-core fiber - Suresh, Mallika; Russell, Philip St. John; Tani, Francesco (Optics Express, 2020)
We present a technique that uses noisy broadband pulse bursts generated by modulational instability to probe nonlinear processes, including infrared-inactive Raman transitions, in molecular gases. These processes imprint correlations between different regions of the noisy spectrum, which can be detected by acquiring single shot spectra and calculating the Pearson correlation coefficient between the different frequency components. Numerical simulations verify the experimental measurements and are used to further understand the system and discuss methods to improve the signal strength and the spectral resolution of the technique.
CRIS-Team Scopus Importer:2020-11-20

Phenomena induced by photoionisation in gas-filled hollow-core photonic crystal fibres - Tani, Francesco; Köhler, Johannes; Suresh, Mallika; Schade, Daniel; Köttig, Felix; Russell, Philip St. John (International Conference on Transparent Optical Networks, 2020)
The optical properties of hollow-core photonic crystal fibre (HC-PCF) can be conveniently tailored by modifying the transverse microstructure and selecting the species and pressure of the gas filling the hollow regions. Additionally, absorption of light by the gas can result in transient changes in refractive index, with characteristic timescales varying from a few hundred femtoseconds to hundreds of microseconds. Understanding the dynamics of these effects is essential for scaling the power and the repetition rate of laser pulse trains launched into HC-PCF, is relevant for pump-probe experiments, and can suggest new ways of controlling the guiding properties of these fibres. Here we review our recent studies, showing measurements of the temporal evolution of local changes in refractive index and describing the novel experimental techniques we developed to investigate the effects.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Nonlinear optics; Photonic crystal fibres